Evaluating social inclusion for the Bangladesh settlers in Nakasi: Post-urban regeneration - Pillay, Shiu Nadan; Palaroan, Rosalie Muertigue (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
This paper examines the concept of the government's 'social housing' policies for the urban poor and assesses their effectiveness. This research aimed to study an upgraded squatter settlement using subdivision and urban renewal concepts and gauge the social effects of the project as experienced by the residents. The paper also suggests how these state-sponsored programs can be improved and enhanced. Thus, it also reviews similar programs in other cities and countries as lessons to be learned. Due to the continuous population growth in the Suva-Nausori corridor, the demand for housing, exceptionally affordable housing, is exponentially growing, and this has led to real estate speculations and bubbles, substandard housing, overcrowding, squatting on public and private lands and homelessness, and this has led to other social problems. A field research study was carried out in 3 lower-income settlements within the affluent district of Nakasi. The findings revealed the need for more government interventions and a more strategic approach to rectify the severe shortfall of housing stock. The paper also notes the importance of the need for a paradigm shift in the state's housing policy to provide low-cost built housing, as opposed to just land length of service, which could not address some crucial issues experienced by the settlers.